FAKTOR PENYEBAB TERJADINYA GELANDANGAN DAN PENGEMIS (Studi Pada Gelandangan dan Pengemis Di Kecamatan Tanjung Karang Pusat Kota Bandar Lampung) - Riskawati, Isma; Syani, Abdul (SOCIOLOGIE, 2013)
This research aimed at assessing the number of beggars and homeless increasingly increase, analyzes about of factors causing existing on the self beggars and homeless so they decided being a vagrant or a beggar. A view of public opposition to the beggars and homeless is lazy, they constitute a human being do not want to work hard to improve his life. There is no single person wants to become a person who lacks house and job that only cadge. City is the main target for them to megadu fate, obtain his fortune in the form of material to the fulfillment of a need. Was chosen because the city as a place of operating for beggars and homeless since the town itself is a crowded place, many shop-house, the market, and other places dsapat made it as a dwelling. While in the afternoon can dujadikan place in search of money to the beggar. In this research used method of qualitative to explain the phenomena that occur in of factors causing the occurrence of beggars and homeless. Using observations and interview means researchers directly with the object research. The determination of an informer done in purposive of sampling that is deliberately with criteria an informant who has been set. Using observation, collecting data interview deep, documentation and the study of pustaka. From the research can be known that beggars and homeless in sub-district tanjung karang central the sub-district is not a native but they are newcomers. Research showed that of factors causing the occurrence of beggars and homeless is presentlyunavailable rests in external and internal factors. The internal factors include poverty, family, age, of physical disabilities low-self education, low skills, the attitudes and mental, while covering the environment, its external factors geographical location and the lack of handling the beggars and homelessKeywords: Homeless, beggars